Efficacy and safety of lasmiditan in patients using concomitant migraine preventive medications: findings from SAMURAI and SPARTAN, two randomized phase 3 trials - Loo, Li Shen; Ailani, Jessica; Schim, Jack; Baygani, Simin; Hundemer, Hans-Peter; Port, Martha; Krege, John H. (Journal of headache and pain, 2019)
Objective To study the efficacy and safety of lasmiditan for acute treatment of migraine in patients using migraine preventive medications. Background While lasmiditan has been proven to be an effective acute treatment for migraine, its effectiveness has not been examined when used concurrently with migraine preventives. Methods SAMURAI and SPARTAN were similarly designed, double-blind, phase 3, placebo-controlled studies of patients 18 years or older with 3 to 8 migraine attacks per month. Patients were randomized to treat a migraine attack with oral lasmiditan 50 mg (SPARTAN only), 100 mg, 200 mg, or placebo. Migraine preventives were allowed as long as doses were stable for 3 months prior to screening and were unchanged during the study. Preventive medications with established or probable efficacy, as recommended by the American Academy of Neurology, the American Headache Society, and the European Headache Federation, plus botulinum toxin type A and candesartan, were included. Within the subgroups of patients using and not using preventive therapies, lasmiditan and placebo groups were analyzed for the outcome of pain-free at 2 h and other efficacy outcomes. The subgroups of patients using and not using preventive therapies were compared and interaction p -values were calculated for safety and efficacy outcomes. Results In these trials, 698 of 3981 patients (17.5%) used migraine preventive treatments. Among patients using preventives, all lasmiditan doses resulted in significantly more patients being pain-free at 2 h, compared to placebo ( p < 0.05). Primary efficacy outcome (pain-free at 2 h), key secondary outcome (most bothersome symptom-free at 2 h) and all other efficacy outcomes were not significantly different between patients using or not using migraine preventives (all interaction p -values ≥0.1). Rates of adverse events were similar for patients using and not using preventive medications. Conclusions Lasmiditan was more effective than placebo for the acute treatment of migraine in patients concurrently using migraine preventive medications. Lasmiditan efficacy and safety measures were similar for patients using and not using preventive medications. Trial registration SAMURAI ( NCT02439320 ) and SPARTAN ( NCT02605174 ). Registered 18 March 2015.